2003
DOI: 10.1073/pnas.0436720100
|View full text |Cite
|
Sign up to set email alerts
|

Functional copper at the acetyl-CoA synthase active site

Abstract: The bifunctional CO dehydrogenase͞acetyl-CoA synthase (CODH͞ACS) plays a central role in the Wood-Ljungdahl pathway of autotrophic CO 2 fixation. A recent structure of the Moorella thermoacetica enzyme revealed that the ACS active site contains a [4Fe-4S] cluster bridged to a binuclear Cu-Ni site. Here, biochemical and x-ray absorption spectroscopic (XAS) evidence is presented that the copper ion at the M. thermoacetica ACS active site is essential. Depletion of copper correlates with reduction in ACS activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
72
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 44 publications
8
72
1
1
Order By: Relevance
“…A promiscuous proximal metal site in cluster A leaves the question of the true catalytic metal open. An essential and functional role of Cu in the ACS͞CODH from acetogenic and methanogenic microorganisms was suggested from the correlation of Cu contents and acetyl-CoA͞CO exchange activities in combination with spectroscopic measurements (15). On the other hand, data have been obtained consistent with a catalytically active Ni 2 -cubane site.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…A promiscuous proximal metal site in cluster A leaves the question of the true catalytic metal open. An essential and functional role of Cu in the ACS͞CODH from acetogenic and methanogenic microorganisms was suggested from the correlation of Cu contents and acetyl-CoA͞CO exchange activities in combination with spectroscopic measurements (15). On the other hand, data have been obtained consistent with a catalytically active Ni 2 -cubane site.…”
supporting
confidence: 62%
“…The Ni-K edge x-ray absorption near edge structure (XANES) of ACS Ch (Fig. 5, which is published as supporting information on the PNAS web site), a finger print for the metal binding motif, differs from the XANES patterns published for the Ni-d site in ACS Mt ͞ CODH Mt (15,44). We attribute these differences to the Ni-p contribution.…”
mentioning
confidence: 40%
See 1 more Smart Citation
“…Several enzyme iron-sulfur centers have been recognized [149,150] [151,152], but it was subsequently shown that the Cu-containing cluster represents an inactivated form of ACS [101]. Similarly, it has also been shown that the open form of the Ni-Ni ACS may switch to a closed, inactivated, form by exchanging one of the nickel atoms for a zinc atom [100].…”
Section: Association Of the Initiating Reactions With Transitionmetalmentioning
confidence: 99%
“…Since XAS accurately reports the structure of metal-protein centers, early workers focused on providing additional high resolution structural and electronic information on crystallographically characterized samples. For instance, XAS enabled detailed structural investigation of metal active sites in imidazolonepropionase 25 , cytochrome P450 26,27 , CO dehydrogenase/acetyl-CoA synthase [28][29][30] , manganese catalases 31,32 , and lipoxygenase 33 by providing key insights into their electronic states and atomic structures. Moreover, insights into the enzymatic reaction mechanisms could be derived from XAS analysis, as was shown for tyrosine hydroxylase 34 , molybdenum(Mo)-nitogenase [35][36][37] , and farnesyltransferase 38 .…”
Section: Application Of Xas In Biologymentioning
confidence: 99%